Comparative Phytochemical Analysis of Chinese and Bay Starvine (Schisandra spp.): Potential for Development as a New Dietary Supplement Ingredient. (2nd November 2017) - Lyles, James T.; Tyler, Paula; Bradbury, E. Jane; Nelson, Kate; Brown, Carl F.; Pierce, Stefanie T.; Quave, Cassandra L.
ABSTRACT: Schisandra chinensis (Chinese starvine) is a popular dietary supplement with a rich history of use in traditional Chinese medicine. Schisandra glabra (bay starvine) is the only North American representative of the genus, and little is known about its history of traditional use, chemistry, and potential biological activity. In this study, we conducted comparative high-performance liquid chromatography-diode array detector (HPLC-DAD) analysis on S. glabra and S. chinensis fruits. Additional characterization of S. glabra was performed by liquid chromatography-Fourier transform mass spectrometry (LC-FTMS). Quantitative analysis of four bioactive marker compounds revealed that S. glabra does not have statistically higher levels of schisandrin A or schisandrol B than S. chinensis . S. glabra has lower levels of schisandrol A and γ-schisandrin. Total phenolic contents of the two species' fruits were not statistically different. S. glabra had higher total tannin content than S. chinensis . We discuss the relevance of this analytical analysis to the study of S. glabra as a potential dietary supplement ingredient and give specific consideration to the conservation challenges involved in commercially developing a regionally threatened species, even in semicultivated conditions.